2020
DOI: 10.22374/ijmsch.v3i1.20
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Psychometric Properties of a Version of the London Measure of Unplanned Pregnancy for Women’s Partners

Abstract: BackgroundThe role of women’s partners in pregnancy planning has gained importance with the development of preconception care. The measurement of pregnancy planning/intention has also changed in the last two decades with the development of psychometric measures such as the London Measure of Unplanned Pregnancy (LMUP). This analysis aimed to evaluate the psychometric properties of a version of the LMUP for women’s partners in the UK. MethodsThe LMUP items, adapted for completion by partners, were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(7 citation statements)
references
References 62 publications
1
6
0
Order By: Relevance
“…14 Lastly, our Mokken Scale analyses indicated a strong scale and showed that items correspond to a basic Guttman structure. 21,31 In line with previous validations, we found that item 1 (contraception) and item 6 (preparation) have the lowest contributions to the scale.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…14 Lastly, our Mokken Scale analyses indicated a strong scale and showed that items correspond to a basic Guttman structure. 21,31 In line with previous validations, we found that item 1 (contraception) and item 6 (preparation) have the lowest contributions to the scale.…”
Section: Discussionsupporting
confidence: 91%
“…This is contrary to what was found in other validations of the LMUP for partners. 21 We expect that this difference was found as a consequence of selection bias, as we expect that partners with more positive feelings towards the pregnancy may be more likely to participate in our studies. This idea is supported by the fact that there was a significant difference in pregnancy intention for people that were linked to their partner in our dataset compared to people that did not have a linked partner.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations